POTENSI DAN DINAMIKA PERTUMBUHAN BAMBU AMPEL DAN BAMBU ORI DI KECAMATAN CANGKRINGAN, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - , RIZKY TRIA NUGRAHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ampel bamboo (Bambusa vulgaris Schrad) and Ori bamboo (Bambusa arundinancea) are kind og bamboo that have economical and ecological benefits. Economical benefir for example is as wood substitution alternatively, and ecological benefit as conservation land and water. This research aims to know potency and dynamical of Ampel and Ori Bamboosâ growths at the district of Cangkringan, according to place height. The research used purposive sampling technique. Inventory is done by putting sample in every village and done track stratification according to place height. Total of sample based on Ampel bamboo land ownership is 21 ownerships and Ori bamboo is 9 bamboo land ownership. Data that is token includes land ownership, land areal wide, place height, diameter, bamboo height, cluster wide, and dynamical of bamboosâ growth. Research result shows that potency sample of Ampel bamboo is as many 26,35 stems/ha, so that is obtained potency of Ampel bamboo at district of Cangkringan is as many 9.918 stems with number of 29 bamboo clusters and potency of Ori bamboo sample is as many 61,56 stems/ha, so that is obtained potency of Ori bamboo potency at district of Cangkringan is as many 56.487 stems with number of 16 bamboo clusters. Average height of Ampel bamboo is as many 9,60 m and average of Ori bamboo is as many 11,65 m. Average stem diameter of Ampel bamboo is as many 9,62 cm and average stem diameter of Ori bamboo is as many 11,44 cm. Average wide of Ampelâs bamboo cluster is as many 1,48 m2, and average wide of Oriâs bamboo cluster is as many 4,81 m2. Dynamical growth of Ampelâs bamboo shoot number is as many 9 bamboo shoots, and number of Oriâs bamboo shoot is as many 2 bamboo shoots, number of Ampel young bamboo is as many 61 stems and number of Oriâs young bamboo is as manu 106 stems, number of Ampelâs old bamboo is as many 266 stems and number of Oriâs old bamboo is as many 214 stems.